Перспективы развития экологического туризма в Республике Крым - Ваниева, А.Р.; Фукала, Д.М. (Культура народов Причерноморья, 2014)
В статье рассматривается сущность понятия «экологический туризм», выявлены
основные проблемы и перспективы устойчивого развития экологического туризма в Республике Крым,
определены факторы, влияющие на реализацию эколого-туристического потенциала региона. Проведен
анализ перспективных направлений развития экологического туризма, что обеспечит повышение
экологической грамотности населения, сохранение природных ресурсов, позволит создать новые
рабочие места и повысить уровень экономики региона. У статті розглядається сутність поняття «екологічний туризм», виявлено основні
проблеми та перспективи сталого розвитку екологічного туризму в Республіці Крим, визначені
фактори, що впливають на реалізацію еколого-туристичного потенціалу регіону. Проведено аналіз
перспективних напрямів розвитку екологічного туризму, що забезпечить підвищення екологічної
грамотності населення, збереження природних ресурсів, дозволить створити нові робочі місця та
підвищити рівень економіки регіону. The article deals with the essence of the concept of «ecological tourism», the main problems and
prospects of sustainable development of ecological tourism in the Republic of Crimea, the factors affecting the
implementation of ecological tourism potential of the region. The analysis of the perspective directions of
development of ecological tourism, which will enhance environmental awareness, conservation, of natural
resources, will create new jobs and improve the economy of the region. Identified the need for information
support of eco-tourism activities, which should be focused on finding mechanisms to ensure prompt access to
information. As one of such mechanisms is the creation of an information network for ecological tourism.
The actual problems of study of one of the most dynamic types of tourism – ethno-cultural tourism, given the
diversity of ethnic and cultural tourism, analyzes the background to the development of ethnic and cultural
tourism. A role in the development of travel with ethno-cultural order can also play protected areas. The
growing popularity of tours which successfully combines elements of ecological and ethnographic tourism,
testifies to the great chances of success of such programs in the region.